Vertical distribution and release characteristics of phosphorus forms in the sediments from the river inflow area of Dianchi Lake, China. Issue 1 (1st January 2018) - Yang, Wan-Qiu; Xiao, Han; Li, Ye; Miao, De-Ren
Abstract: Columnar sediment samples were collected from five representative river inflow areas of Dianchi Lake, China. The vertical distribution of each form of P were tested. Results showed that the concentration of TP in the sediments from areas A, B, C, D and E in the order of D > B > A > C > E, and the average concentration of D, B, A, C and E were 2991, 2064, 1308, 879, and 759 mgkg −1, respectively. The concentration of Ex-P, Fe/Al-P, Ca-P and Org-P all decreased with increasing depth. The release of Ex-P was significantly related to TP whereas the Fe/Al-P was not significantly related to TP in the samples from areas polluted by domestic sewage. However, the release of Ex-P and Fe/Al-P were both significantly related to TP in the samples from areas polluted by phosphate mining and phosphate fertilizer application. The results of equilibrium P concentration (EPC0) analysis showed that P in the sediments of areas A, D and E were the source of P in Dianchi Lake, and the P in the sediments of areas B and C were in relative equilibrium with the overlying water.